2004
DOI: 10.1242/jeb.01055
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia tolerance and preconditioning are not additive in the trout(Oncorhynchus mykiss) heart

Abstract: Research has shown that the trout heart is normally hypoxia-sensitive, and that it can be preconditioned. However, we have identified a group of rainbow trout Oncorhynchus mykiss that shows a surprising degree of myocardial hypoxia tolerance. In this study, we used in situ hearts from these fish as a comparative model to examine whether the cardioprotective effects afforded by hypoxic adaptation and preconditioning are additive. In situ trout hearts were exposed to severe hypoxia (perfusate P O∑ 5-10·mmHg) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…This is because, in contrast to the rainbow trout (e.g. Faust et al, 2004;Gamperl et al, 2004), acute exposure of the in situ cod heart to severe hypoxia does not affect ƒ H during resting or maximum levels of cardiac performance (Petersen and Gamperl, 2010), and maximum ƒ H and scope for ƒ H were not different in hypoxiaacclimated cod when swum under hypoxic and normoxic conditions (Fig.2, Table3). Furthermore, it is unlikely that the lowered ƒ H was the result of the stimulation of branchial O 2 receptors as this level of hypoxia (8-9kPa) did not elicit bradycardia under resting conditions.…”
Section: Effects Of Acute Hypoxia: Exercisementioning
confidence: 89%
“…This is because, in contrast to the rainbow trout (e.g. Faust et al, 2004;Gamperl et al, 2004), acute exposure of the in situ cod heart to severe hypoxia does not affect ƒ H during resting or maximum levels of cardiac performance (Petersen and Gamperl, 2010), and maximum ƒ H and scope for ƒ H were not different in hypoxiaacclimated cod when swum under hypoxic and normoxic conditions (Fig.2, Table3). Furthermore, it is unlikely that the lowered ƒ H was the result of the stimulation of branchial O 2 receptors as this level of hypoxia (8-9kPa) did not elicit bradycardia under resting conditions.…”
Section: Effects Of Acute Hypoxia: Exercisementioning
confidence: 89%
“…Furthermore, they have proved to be a very valuable tool for understanding teleost heart function during periods of oxygen deprivation Arthur et al, 1992;Hanson and Farrell, 2007), the importance of circulating catecholamines in supporting cardiac function under conditions experienced during severe exercise [e.g. hypoxemia, hyperkalemia and acidosis (Hanson et al, 2006;Hanson and Farrell, 2007)], and for elucidating several aspects of preconditioning in the teleost heart (Gamperl et al, 2001;Gamperl et al, 2004;Faust et al, 2004;Overgaard et al, 2004b). Thus, the present study used in situ heart preparations to investigate the effects of acclimation to hypoxia on the normoxic and hypoxic performance of the Atlantic cod heart, and ultimately to determine whether the reduced in vivo cardiac performance observed in hypoxia-acclimated cod (Petersen and Gamperl, 2010) was a direct result of a decrease in the pumping capacity of the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Gamperl et al (2001) reported that hearts of hypoxia-intolerant rainbow trout can be preconditioned such that an initial 5-min period of acute severe hypoxia can abolish the myocardial dysfunction induced by a further 30-min period of hypoxia. However, Gamperl et al (2004) and Overgaard et al (2004) also demonstrated, in hypoxia-tolerant rainbow trout, that such hypoxia pre-conditioning had no protective effect to a further bout of severe hypoxia. Given their hypoxia-tolerance, tambaqui may respond to hypoxic pre-conditioning in a similar manner to hypoxiatolerant trout.…”
Section: Effects Of Hyperoxia Hypoxia and Hypercapnia On Nacn-evokedmentioning
confidence: 95%